Identifying Factors Associated with Health Problems of Tannery Workers, Savar, Dhaka: Factors Associated with Health Problems of Tannery Workers (Dhaka University Journal of Science, 2024)
This research investigates the incidence and patterns of health problems experienced by tannery employees, as well as the associations between such problems and a variety of other variables. The cross-sectional study was conducted at three randomly selected tanneries of the BSCIC Tannery Industrial Estate in Savar. During in-person interviews, 203 workers were questioned using a questionnaire. Most respondents (84.2%) admitted that they had health problems caused by their jobs. Musculoskeletal disease (65.5%), gastrointestinal problems (38.9%), skin disease (37.9%), respiratory disease (26.6%), and eye disease (17.7%) were the significant causes of illness. Our research revealed that factors such as respondents' age (p value=.001), experience (p value